2019
DOI: 10.11114/ijsss.v7i2.4017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Need for Belongingness and Facebook Addiction: Mediating Role of Number of Friends on Facebook

Abstract: As humans, we need to connect with one another, our friends and families, our culture and country. Present age is the era of information and technology and social media. College and University students spend significant amount of time on Social Networking Sites like Facebook etc. The present study was conducted to explore role of number of friends on Facebook on the relationship between individual's need for belongingness and Facebook addiction. A sample of 180 university students was selected as sample throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“… Seidman (2013) stated that satisfying the need to belong and acceptance are major motivations for Facebook usage, and individuals who use social media might increase their self-esteem and sense of belongingness. Furthermore, there are some studies which detected positive relationships between social media and the need to belong (e.g., Casale & Fioravanti, 2018 ; Hodgins, 2015 ; Rashid et al, 2019 ). Nonetheless, these results should be considered differently according to ordinary usage of social media and social media addiction, because addictive usage might trigger some interpersonal troubles and withdrawal ( Chen et al, 2003 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“… Seidman (2013) stated that satisfying the need to belong and acceptance are major motivations for Facebook usage, and individuals who use social media might increase their self-esteem and sense of belongingness. Furthermore, there are some studies which detected positive relationships between social media and the need to belong (e.g., Casale & Fioravanti, 2018 ; Hodgins, 2015 ; Rashid et al, 2019 ). Nonetheless, these results should be considered differently according to ordinary usage of social media and social media addiction, because addictive usage might trigger some interpersonal troubles and withdrawal ( Chen et al, 2003 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have reported that the Facebook addiction is a common problem among students and youth generations [24], [24], [40], [42], [44]. Although, Facebook addiction had received slightly consideration in the literature and founded that Facebook addiction have positive correlation with Facebook motives such as entertainment, communication and social interaction [10], [17], [40], [44], [58], [63], [64]. Further, its argued that the Facebook addiction is related with being male, being a heavy Facebook user [65], being in a higher year level at university [24].…”
Section: B Facebook Addictionmentioning
confidence: 99%
“…In recent years, it has been recognized that the Facebook Addiction has become the considerably more important. Several studies have been conducted on this topic [12], [17], [28], [40], [41], [41], [42]. It is reported that Facebook addiction has become a universal concern and considered as a health issue [43], although it has been a worldwide problem among university students and youth generation [2], [10], [17], [28], [40], [42], [44].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations